The discovery of a localized colony of Brithys crini (Fabricius, 1775) in the Maltese archipelago (Lepidoptera: Noctuidae) - Catania, Aldo; Mifsud, Stephen (SHILAP Revista de lepidopterología, 2024)
Brithys crini (Fabricius, 1775) is here recorded after many years from the Maltese archipelago.